What to do next to control the 2019-nCoV epidemic? - Wang, Fu-Sheng; Zhang, Chao (The Lancet (British edition), 2020)
Notably, 159 confirmed cases have been reported in 23 other countries beyond China, including Japan, Thailand, Singapore, South Korea, Australia, the USA, Malaysia, and Germany. Because of the seriousness of this outbreak, WHO declared it a public health emergency of international concern on Jan 30, 2020, followed by the USA announcing a public health emergency on Jan 31, 2020. [...]it is important to understand the lung microenvironment and the map of immune responses against 2019-nCoV infection, which might help to define clinical stages and uncover the pathogenesis of the disease. First-line medical staff and scientists in China have had a leading role in fighting the outbreak of 2019-nCoV-associated pneumonia.